2008
DOI: 10.1111/j.1567-1364.2007.00314.x
|View full text |Cite
|
Sign up to set email alerts
|

Kwoniella mangroviensisgen. nov., sp. nov. (Tremellales,Basidiomycota), a teleomorphic yeast from mangrove habitats in the Florida Everglades and Bahamas

Abstract: Mangrove forests inhabit the shoreline regions of tropical and subtropical marine habitats, where they are the basis of a multi-trophic level food web that drives the shellfish and fisheries industries. Yeasts, and other fungi, have significant roles in these ecosystems as they decompose plant organic material and serve as a food source for small invertebrates. Studies designed to examine yeast communities of mangrove regions of the Florida Everglades and the Bahamas demonstrated the repeated presence of an un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
36
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 25 publications
1
36
0
Order By: Relevance
“…They also determined LSU and ITS sequences for representative strains and found little genetic variability, except for one cork isolate and the beach isolate, which had one nucleotide substitution in LSU and 6 to 7 substitutions in ITS, compared to the mangrove strains. These differences were not considered sufficient by Statzell-Tallman et al (13) to warrant separate taxonomic status for those strains without further mating and genetic studies.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…They also determined LSU and ITS sequences for representative strains and found little genetic variability, except for one cork isolate and the beach isolate, which had one nucleotide substitution in LSU and 6 to 7 substitutions in ITS, compared to the mangrove strains. These differences were not considered sufficient by Statzell-Tallman et al (13) to warrant separate taxonomic status for those strains without further mating and genetic studies.…”
Section: Discussionmentioning
confidence: 94%
“…In the present study, we have complemented the MLST approach with the analysis of MAT genes due to the central role played by MAT loci in regulating sexual reproduction and thus in determining species boundaries (1,3). The multilocus approach involved five K. mangrovensis strains (four from seawater and one from cork) from the original study (13), as well as one additional isolate from the British Virgin Islands, one clinical isolate from the United States, four isolates from Mopane trees in Botswana, one isolate from a tree hollow in Brazil, and two isolates from grapes in Europe (see Table S1 in the supplemental material). The results showed that the tropical seawater isolates, which included the type strain of K. mangrovensis, formed a monophyletic lineage, while the four Botswana isolates and the three European strains formed two additional sister lineages ( Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations